Indigenous america eaudiobook - McDonald, Liam (True History., 2022)
“A powerful series that fills in the cracks and illuminates the shadows of the past.” –Sherri L. Smith, award-winning author of Flygirl   Introducing a new nonfiction series that uncovers hidden histories of the United States. The true story of the United States’ Indigenous beginnings. American schoolchildren have long been taught that their country was “discovered” by Christopher Columbus in 1492. But the history of Native Americans in the United States goes back tens of tens of thousands of years prior to Columbus’s and other colonizers’ arrivals. So, what’s the true history?  Indigenous America introduces and amplifies the oral and written histories that have long been left out of American history books.